Intervensi Komitmen Organisasional Pada Pengaruh Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB)(Studi Dalam Setting Organisasi Kemahasiswaan) - Meika Kurnia Puji Rahayu; Septi Ani Qurdiana (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
This research aims to analyze the role of organizational commitment in intervening the influence of job satisfaction toward organizational citizenship behavior (OCB), particularly in student organizational setting. Research subject is member of Himpunan Mahasiswa Manajemen (HIMAMA), a student organization in the Dapertment of Management, Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta. Sample was determined through purposive sampling, yielded 102 respondents. Data was collected using questionnaires, and then analyzed using Structural Equation Modeling (SEM) with AMOS software. The research findings confirm that organizational commitment acts as intervening variable on the influence of job satisfaction toward OCB.